ON THE DESIGN CONSIDERATIONS OF A 1.5 MVA WIND ENERGY SYSTEM - Mese, Erkan; Atalan, Mertcan (IEEE, 2011)
This paper outlines critical steps to be taken during design of a wind power generation and utility interfacing system. These steps include determining generator open circuit voltage, utility and DC bus voltages, determining topologies for rectifiers and inverters, examining power control strategies, sizing active and passive components in the entire system.
Keywords: Wind energy; Voltage Source Converter; Pulse Width Modulation (PWM); Harmonics; Permanent magnet motor; Engineering